A Comparative Analysis of Dental Measurements in Physical and Digital Orthodontic Case Study Models - Elena-Raluca Baciu; Dana Gabriela Budală; Roxana-Ionela Vasluianu; Costin Iulian Lupu; Alice Murariu; Gabriela Luminița Gelețu; Irina Nicoleta Zetu; Diana Diaconu-Popa; Monica Tatarciuc; Giorgio Nichitean; Ionuț Luchian (Medicina, 2022)
Background and Objectives: Study models are essential tools used in the dental teaching process. The aim of the present study was to compare the values obtained by manual and digital orthodontic measurements on physical and digital case study models. Materials and Methods: The physical experimental models were obtained by traditional pouring (improved stone-type IV gypsum products) and by additive manufacturing (resins). The digital experimental models were created by scanning the physical ones, using a white light-emitting diode (LED) source and an L-shaped dental scanner—Swing DOF (DOF, Seoul, Korea). The physical study models were first measured using a digital caliper, and then, they were scanned and evaluated using the DentalCad 3.0 Galway software (exocad GmbH, Darmstadt, Germany). The Pont, Linder–Harth, and Bolton indices, which are used in orthodontics for training students, were derived using the available data. Results: When comparing the linear measurement mean ranks taken on physical study models to those of digital models, no statistically significant differences (p > 0.05) were found. A similar result was also shown when the dentoalveolar growth indicators were analyzed. Conclusions: It can be concluded that dental study models made by direct light processing (DLP) and pouring type IV class gypsum are both acceptable for orthodontic teaching purposes.